Pemberdayaan Dan Edukasi Terhadap Orang Tua Anak Berkebutuhan Khusus Penyandang Autisme Di Wilayah Kabupaten Garut - Intan, Tania (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The activities of the PMM are a form of Community Service at Padjadjaran University. For 2019, the proposing team has designed an activity themed Empowerment and Education for Parents of Children with Special Needs for People with Autism in Garut Regency Area by involving two related communities. First, APPAI (Association of Indonesian Autism Practitioners and Observers), a combination of various elements of the community who have concern and desire to contribute to the protection and handling of children with special needs for autism in Indonesia. The second, Portadin (Parents Association of Indonesian Disabled Children) Garut DPD is a community that accommodates ABK parents with autism in Garut. From the results of preliminary observations and the interaction of the team with the community of parents of children with special needs, it was found that there were problems in the form of knowledge and motivation constraints of parents in facing the special conditions of their children. Through PKM activities, data collection, counseling and dialogue with the target audience above are conducted, guided by experts, as a form of empowerment and education. This activity is problem solving, comprehensive, meaningful, complete, and sustainable. The phenomenological qualitative method was chosen because it is a thinking view that emphasizes the focus on subjective experiences (data revealed based on the subject's point of view) of humans and world interpretations. The steps of the activity include: preparation, implementation, and evaluation stages.